The Influence of Social Media Advertising Exposure and Influencer Credibility on Brand Awareness and Purchase Intention - Ida Ayu Trisna Wijayanthi; Ni Ketut Laswitarni (Malaqbi Publisher, 2026)
The rapid growth of social media has significantly transformed marketing communication strategies, enabling companies to promote their products through digital advertising and influencer collaborations. This study aims to examine the influence of social media advertising exposure and influencer credibility on brand awareness and purchase intention. A quantitative research approach was employed using a survey method to collect primary data from 200 social media users who had been exposed to online advertisements and influencer promotional content. The data were analyzed using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) technique. The results indicate that social media advertising exposure has a significant positive effect on brand awareness and purchase intention. Similarly, influencer credibility was found to significantly influence both brand awareness and purchase intention. The findings also reveal that brand awareness has a significant positive effect on purchase intention, indicating that consumers who are familiar with and recognize a brand are more likely to develop intentions to purchase its products. These results highlight the important role of social media advertising and influencer credibility in enhancing brand awareness and encouraging consumer purchase behavior in the digital marketing environment. The study provides practical implications for marketers by emphasizing the importance of consistent advertising exposure and collaboration with credible influencers to strengthen brand visibility and increase consumer purchase intentions.